The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/anec.12224
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Exercise‐Induced T‐Wave Alternans Predictive Power for the Occurrence of Ventricular Arrhythmias from Heart Rate

Abstract: Exercise-induced TWA predictive power for the occurrence of ventricular arrhythmias, quantified using both maxTWAA and TWAAratio, was higher at low rather than at high HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Still, such HR range was not optimal to discriminate ICD_Cases from ICD_Controls (Table ), that is to identify those ICD patients who developed VT/VF during follow‐up, and thus who were retrospectively identified as at increased risk of major cardiac events. Similarly to what found in our previous studies, the best exercise HR for discriminating the two ICD groups was 80 bpm, in correspondence of which ICD_Cases and ICD_Controls were characterized by low but significantly different TWA levels, with the former showing higher TWA than the latter (Table ). Such HR also represents a common HR at which arrhythmias occur, observation that supports the hypothesis of TWA being an arrhythmogenic phenomenon.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Still, such HR range was not optimal to discriminate ICD_Cases from ICD_Controls (Table ), that is to identify those ICD patients who developed VT/VF during follow‐up, and thus who were retrospectively identified as at increased risk of major cardiac events. Similarly to what found in our previous studies, the best exercise HR for discriminating the two ICD groups was 80 bpm, in correspondence of which ICD_Cases and ICD_Controls were characterized by low but significantly different TWA levels, with the former showing higher TWA than the latter (Table ). Such HR also represents a common HR at which arrhythmias occur, observation that supports the hypothesis of TWA being an arrhythmogenic phenomenon.…”
Section: Discussionsupporting
confidence: 83%
“…Microvolt T‐wave alternans (TWA) consists in a subtle every‐other‐beat fluctuation of the electrocardiographic (ECG) T‐wave amplitude at stable heart rate (HR) during sinus rhythm, and is considered a promising noninvasive index to predict the occurrence of malignant ventricular arrhythmias and sudden cardiac death . It has been observed that TWA tends to increase its amplitude with increasing HR so that, even though it has also been observed in resting conditions, TWA analysis is often performed at accelerated HRs reached through exercise . Several studies have shown that exercise‐induced TWA is capable of stratifying risk for cardiovascular death and lethal arrhythmias .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Microvolt T-wave alternans (TWA), consisting in a subtle alternation of the electrocardiographic (ECG) T wave, is a promising noninvasive indicator of sudden cardiac death [9]. Although low-levels of TWA have been also observed in resting healthy subjects [10,11,12], TWA is more commonly found in patients affected by cardiovascular diseases [11,13,14,15,16] and its amplitude tends to increase with increasing heart rate (HR) [9,17,18]. As a consequence, since HR decrease during sleep and TWA is more hardly detectable, only few studies have investigated TWA incidence during sleep, especially when SA occurs [7,19].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that TWA depends on HR. Specifically, it has been observed that TWA tends to increase with increasing HR [6][7][8][9] so that, even though it has also been observed in resting conditions [10][11][12][13], TWA analysis is often performed at accelerated HRs reached through exercise [1,[4][5][6][7][8][9]14,15].…”
Section: Introductionmentioning
confidence: 99%